Historical trends of homicide and road traffic fatalities in South Africa: 1968–1989. (1st March 2011) - Prinsloo, M; Bradshaw, D; Laubscher, R
Abstract : Introduction: South Africa has a high injury burden, with homicide and road traffic injuries (RTI) being the leading causes of injury death. There is little information about long-term trends. Good quality vital statistics are available for 1968–1989 for selected population groups and will be analysed towards understanding the historical pattern of violence and road deaths within South Africa. Method: Unidentified unit record cause of death data with ICD-9 coding were obtained from the national statistical office for 1968–1989, including population groups assigned during the Apartheid-era, age and sex. Trends in injury proportions due to homicide and RTI and the ratio of homicide to suicide were examined by population group. Age standardised rates will be calculated for whites, coloureds and Indians since data for Blacks are incomplete. Results: RTI as a proportion of total injuries were highest for whites and Indians at approximately 42% and 35% respectively. At 6–10 homicides for every suicide, the ratio for coloureds was fairly constant until 1980, after which it increased sharply for coloureds and Blacks. For whites the ratio was <1 over the period, while for Indians the ratio ranged between <1 and 2.5. Age standardised rates will also be presented. Conclusion: Preliminary results indicate that homicides were considerably higher for coloureds and Blacks than for whites and Indians, with increases during the last stages of Apartheid. While fatal RTIs appear to have remained fairly constant, decreases which may have been associated with petrol restrictions during the global oil crisis were noticed.